Dimensions of trust: A review of trust in government - Tanny, Tahmina Ferdous (Indian Journal of Public Administration)
This article explains different dimensions of trust relevant to trust in government and, therefore, suggests a brief model for practical application. The study pursues content analysis method for theoretical treatment of knowledge produced from studying secondary sources of literature. Imitating the context, the concept of trust is clarified first, and then dimensions of trust are arranged under two broad heads: institutional trust and social trust. And then follow the analyses and the subdivisions thoroughly. A compendious model is suggested with possible solutions for public trust in government. Explanations claim that aggregation of institutional trust, that is, political, administrative and social trust, might build an array of trustworthy governance, though adequate pertinent literature are not easily available. This paper recommends that trust in government model may be tested for further empirical study.- Reproduced
Keywords: Trust, Dimensions, of trust, Political trust, Trust in public administration